Variable-speed wind energy conversion system based on a dual stator-winding induction generator - Barrado, Jose Antonio (2017)
This study presents a wind energy conversion system based on a dual stator-winding induction generator. The generator can work at variable wind speed and can also be connected to the grid. The proposed energy conversion system presents three operation zones that depend on the wind speed and are delimited by the power ratio assigned to each of the two stator windings. The generator design starts from a three-phase squirrel-cage induction machine and allows a simple assembling of the new windings, what results in an economical, robust and reliable machine. These features make the generator appropriate for wind energy conversion systems located in remote places or in developing areas with limited resources, as well as for distributed generation systems and microgrids. This report also includes experimental and simulation results of the generator operation in the three working areas.